2017
DOI: 10.1016/j.jacc.2016.10.086
|View full text |Cite|
|
Sign up to set email alerts
|

Trending Cardiovascular Nutrition Controversies

Abstract: The potential cardiovascular benefits of several trending foods and dietary patterns are still incompletely understood, and nutritional science continues to evolve. However, in the meantime, a number of controversial dietary patterns, foods, and nutrients have received significant media exposure and are mired by hype. This review addresses some of the more popular foods and dietary patterns that are promoted for cardiovascular health to provide clinicians with accurate information for patient discussions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 129 publications
2
75
0
8
Order By: Relevance
“…Coconut oil is also associated with increased levels of cholesterol, 45,46 LDL cholesterol, 11 and the chance of CVD due to its high SFA concentration. 31,47 Our results demonstrated that rats fed with HFD and supplemented with VCO have high levels of plasma lipid peroxidation. In addition, as a compensatory response to oxidative damage caused by chronic exposure to HFD and VCO, the animals presented an increase in the activity of antioxidant enzymes SOD, CAT, and GPx.…”
mentioning
confidence: 54%
“…Coconut oil is also associated with increased levels of cholesterol, 45,46 LDL cholesterol, 11 and the chance of CVD due to its high SFA concentration. 31,47 Our results demonstrated that rats fed with HFD and supplemented with VCO have high levels of plasma lipid peroxidation. In addition, as a compensatory response to oxidative damage caused by chronic exposure to HFD and VCO, the animals presented an increase in the activity of antioxidant enzymes SOD, CAT, and GPx.…”
mentioning
confidence: 54%
“…Plant-based diets consist of predominantly plant foods and a low intake of animal foods (1,2). Research has shown that plant-based diets are associated with lower risk of obesity, type 2 diabetes, hypertension, and cardiovascular disease (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Správný stravovací režim je základním kamenem prevence i léčby KVO, i když je nutné připustit, že přesné vysvětlení výhod konzumace některých potravin vzhledem k manifestaci onemocnění, není dosud zcela jednoznačně formulováno. 25 Výzkum vlivu výživy na KVO probíhá, včetně validní statistické analýzy výsledků, studie případů a kontrol a z pohledu poměru nákladů a přínosů (cost--effectiveness ratio) je třeba říci, že tyto studie nejsou drahé a přinášejí nové poznatky, které pomáhají lépe formulovat a upřesnit doporučení týkající se nefarmakologických opatření k ovlivnění kardiovaskulárních onemocnění. 5 Podle Světové zdravotnické organizace většina hlavních faktorů, které se uplatňují nepříznivě ve vztahu ke zdraví člověka, souvisí s výživou.…”
Section: Dietní Opatřeníunclassified